Tunable phenotypic variability through an autoregulatory alternative sigma factor circuit - Schwall, Christian P; Loman, Torkel E; Martins, Bruno M C; Cortijo, Sandra; Villava, Casandra; Kusmartsev, Vassili; Livesey, Toby; Saez, Teresa; Locke, James C W (Molecular systems biology, 2021)
Genetically identical individuals in bacterial populations can display significant phenotypic variability. This variability can be functional, for example by allowing a fraction of stress prepared cells to survive an otherwise lethal stress. The optimal fraction of stress prepared cells depends on environmental conditions. However, how bacterial populations modulate their level of phenotypic variability remains unclear. Here we show that the alternative sigma factor σ V circuit in Bacillus subtilis generates functional phenotypic variability that can be tuned by stress level, environmental history and genetic perturbations. Using single‐cell time‐lapse microscopy and microfluidics, we find the fraction of cells that immediately activate σ V under lysozyme stress depends on stress level and on a transcriptional memory of previous stress. Iteration between model and experiment reveals that this tunability can be explained by the autoregulatory feedback structure of the sigV operon. As predicted by the model, genetic perturbations to the operon also modulate the response variability. The conserved sigma‐anti‐sigma autoregulation motif is thus a simple mechanism for bacterial populations to modulate their heterogeneity based on their environment. SYNOPSIS A combination of single‐cell imaging and mathematical modelling reveals a simple mechanism for bacterial populations to modulate their heterogeneity based on their environment and environmental history. The time to activate the alternative sigma factor σ V in Bacillus subtilis is found to be heterogeneous under lysozyme stress. This phenotypic variability can be tuned by stress levels, previous stress applications, and genetic perturbations. Modelling and experiments show that this tunability can be explained by the structure of the sigV operon, which consists of a ‘mixed’ positive and negative feedback loop. Graphical Abstract A combination of single‐cell imaging and mathematical modelling reveals a simple mechanism for bacterial populations to modulate their heterogeneity based on their environment and environmental history.